2019
DOI: 10.3390/cancers11070954
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mode of Action of TRAIL Receptor Agonists—Common Principles and Their Translational Exploitation

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and its death receptors TRAILR1/death receptor 4 (DR4) and TRAILR2/DR5 trigger cell death in many cancer cells but rarely exert cytotoxic activity on non-transformed cells. Against this background, a variety of recombinant TRAIL variants and anti-TRAIL death receptor antibodies have been developed and tested in preclinical and clinical studies. Despite promising results from mice tumor models, TRAIL death receptor targeting has failed so far in cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 151 publications
(144 reference statements)
1
32
0
Order By: Relevance
“…However, the potential mechanism of that is still unclear and no effective therapeutic agents have been found. The literature has shown that oligomerization of DR5 death domain in plasma membrane recruiting FADD results in FADD activating caspase 8 and the following caspase 3 cascade, the process of that represents the formation of the DISC a nd initiates the extrinsic apoptotic pathway 35,36 . In our study, caspase 8 and FADD were key molecules for NaAsO 2 ‐induced DISC formation and DR5 was a mediator in NaAsO 2 ‐induced apoptosis of L‐02 cells by promoting the formation of DISC and activating caspase cascade.…”
Section: Discussionsupporting
confidence: 51%
“…However, the potential mechanism of that is still unclear and no effective therapeutic agents have been found. The literature has shown that oligomerization of DR5 death domain in plasma membrane recruiting FADD results in FADD activating caspase 8 and the following caspase 3 cascade, the process of that represents the formation of the DISC a nd initiates the extrinsic apoptotic pathway 35,36 . In our study, caspase 8 and FADD were key molecules for NaAsO 2 ‐induced DISC formation and DR5 was a mediator in NaAsO 2 ‐induced apoptosis of L‐02 cells by promoting the formation of DISC and activating caspase cascade.…”
Section: Discussionsupporting
confidence: 51%
“…Experimental data support receptor oligomerization of TRAIL and other TNFRSF receptors on the cell surface but there have been conflicting models proposed over the years [4,6,13,14]. Activating several receptors all at once by their corresponding membrane-bound ligands necessitates that both the receptors and the ligands are arranged with the same geometry, which rules out random receptor/ligand arrangement on the cell surface.…”
Section: Receptors and Ligands Need To Cluster In A Highly Ordered Mamentioning
confidence: 99%
“…In addition, because TRAIL provides an external trigger for apoptosis, it has the potential to overcome resistance to internal triggers of apoptosis after radiation or chemotherapy. There have been many excellent reviews on TRAIL biology and the mechanism of action with implication for therapeutic applications in recent years [2][3][4][5][6][7][8]. Here, we focus on the structure-function of TRAIL and extend our discussion to other members of the TNFSF/TNFRSF to illustrate the mechanism of signaling by reviewing the most up-to-date and relevant information from the scientific literature.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo experiments showed that previously tested DR5 agonist immunoglobulin G (IgG) antibodies required secondary antibody crosslinking via Fc gamma receptor (FcγR)-expressing effector cells for optimal DR5 clustering and apoptosis induction (6,7). The limited success of DR5 antibodies in clinical trials may be the result of insufficient FcγR-mediated crosslinking in the tumor microenvironment (8)(9)(10). Alternative mechanisms to induce aggregation and clustering independent of FcγR have also been explored, but limited efficacy data have been published, and in some cases adverse events and toxicity signals were observed (3,11,12).…”
Section: Introductionmentioning
confidence: 99%